Effect of cultivation method and processing on total polyphenols content and antioxidant capacity of tomatoes (Solanum lycopersicum) - Peralta, Mariana Isabel; Fuentes, Karen Noelia; Canalis, Alejandra Mariel; Soria, Elio Andrés (Nutrición Clínica y Dietética Hospitalaria, 2020)
Introduction: Tomato is an important dietary source of polyphenols. Factors such as cultivation method and heat can affect its composition. The objective of this study was to determine changes of polyphenol content and antioxidant capacity in tomatoes obtained from different production method (organic vs. conventional), before and after being cooked. Methods: Total polyphenols and antioxidant capacity were measured in fresh and processed tomatoes from two cultivation methods, using spectrophotometric techniques. Results: Antioxidant capacity was higher (p<0.05) for fresh and processed samples of organic tomatoes compared with conventional ones (organic 17,82 mg Fe+2/g > conventional 15,39 mg Fe+2/g). No significant difference in polyphenol content according to method of cultivation was found (organic 3,8 μg GAE/g > conventional 3,2 μg GAE/g). Measured parameters were not significantly affected by physical and mechanical processing in tomatoes from both cultivation methods. Discussion: A tendency towards better phytochemical properties in organic tomatoes were found in our study, which is consistent with existing literature. Antioxidant compounds in organic samples appear to be more resistant to processing. Conclusion: It is necessary to deepen the study of organic and conventional tomatoes, in order to get more evidence on its nutritional quality.